2017
DOI: 10.1016/j.btre.2017.10.004
|View full text |Cite
|
Sign up to set email alerts
|

High-throughput microarray for antimicrobial susceptibility testing

Abstract: HighlightsDeveloped a high-throughput microarray for anti-microbial susceptibility testing (AST).Demonstrated that the feasibility of the AST against clinical isolates of MRSA.Platform is a low sample volume, rapid, high-throughput alternative to traditional assays.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Various attempts have been made to create bacteria immobilization platforms for performing highly parallelized and automated AST. A nanoarray of spotted antimicrobial-impregnated hydrogel was devised on which microbial samples could be layered . After incubation, the array could be stained and imaged to determine antimicrobial susceptibility.…”
Section: Emerging Innovative Sensing Technologies For Amr Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…Various attempts have been made to create bacteria immobilization platforms for performing highly parallelized and automated AST. A nanoarray of spotted antimicrobial-impregnated hydrogel was devised on which microbial samples could be layered . After incubation, the array could be stained and imaged to determine antimicrobial susceptibility.…”
Section: Emerging Innovative Sensing Technologies For Amr Managementmentioning
confidence: 99%
“…A nanoarray of spotted antimicrobial- impregnated hydrogel was devised on which microbial samples could be layered. 56 After incubation, the array could be stained and imaged to determine antimicrobial susceptibility. Similarly, hydrogel immobilization AST platforms (Figure 1B) have been developed to allow for automatic monitoring of microbial growth in response to antimicrobial challenge.…”
Section: ■ Emerging Innovative Sensing Technologies For Amr Managementmentioning
confidence: 99%
“…As in the case of C. albicans , the resulting miniaturized bacterial biofilms demonstrated characteristics similar to those displayed by conventionally formed macroscopic biofilms for the two species, including architectural features (Figure 2), synthesis of biofilm matrices, and high levels of resistance to antibiotics [30]. In an extension of these studies, most recently we demonstrated the applicability of a similar technique for culturing community acquired methicillin resistant Staphylococcus aureus (CA-MRSA), and perform antibiotic susceptibility testing against clinical isolates of CA-MRSA, which required significantly smaller sample volumes compared to conventional methods and resulted in much faster results [31].…”
Section: Expansion To Bacterial and Polymicrobial Biofilmsmentioning
confidence: 99%
“…Spontaneous aggregation driven by low-shear conditions either in a shake flask or by magnetic levitation also produces biofilm-like morphological and drug susceptibility characteristics ( 13 , 14 ). We have shown that biofilms of single and polymicrobial nanocultures of Candida albicans , S. aureus , and P. aeruginosa encapsulated in alginate or collagen grow as dense microcolonies, express copious exopolymeric matrix, and show increased antibiotic resistance ( 15 17 ). Our nanoculture microarray platform not only facilitated ultrahigh-throughput screening of antibiofilm drugs but also prompted insights into the possibility of biofilm formation in three dimensions instead of traditional, gravity-driven surface attachment in two dimensions as a prerequisite first step.…”
Section: Introductionmentioning
confidence: 99%